2015
DOI: 10.7314/apjcp.2015.16.14.5625
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of β-catenin Expression in Breast Cancer Patients: a Meta-analysis

Abstract: Background: β-catenin plays a crucial role in the progression of breast cancer (BC) and a prognostic role of in BC patients has been widely reported. However, controversy still remains. Materials and Methods: Identical search strategies were used to search relevant literature in electronic databases updated to July 1, 2014. Individual hazard ratios (HRs) and 95% confidence intervals (CIs) were extracted and pooled HRs with 95%CIs were used to evaluate the strength of association between positive β-catenin expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…Zeng et al (52) also suggested that altered expression of β-catenin could serve as a predicative factor of poor prognosis for patients with esophageal carcinoma. Zhang et al (50) and Chen et al (53) have demonstrated that positive β-catenin expression in cytoplasm/nucleus was significantly associated with poor prognosis of breast cancer and hepatocellular carcinoma respectively. Combined with our meta-analysis, these findings suggest that aberrant β-catenin expression predicts a poor survival in a wide variety of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng et al (52) also suggested that altered expression of β-catenin could serve as a predicative factor of poor prognosis for patients with esophageal carcinoma. Zhang et al (50) and Chen et al (53) have demonstrated that positive β-catenin expression in cytoplasm/nucleus was significantly associated with poor prognosis of breast cancer and hepatocellular carcinoma respectively. Combined with our meta-analysis, these findings suggest that aberrant β-catenin expression predicts a poor survival in a wide variety of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out a meta-analyses of β-catenin expression in NSCLC patients based on 24 studies (Table 1), while Yang et al (46) recently reported a meta-analyses of expression in NSCLC patients based on 15 studies. Membranous β-catenin that is directly associated with E-cadherin and α-catenin is involved in the stabilization of cell-cell adhesion, whereas cytoplasmic and nuclear β-catenin are important mediators of the canonical Wnt signaling cascade (47)(48)(49)(50). The association between overall β-catenin expression and prognosis of NSCLC patients is controversial (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have proven that nuclear β-catenin overexpression predicts progressive disease and unfavorable survival in colorectal cancer [25], lung cancer [26, 27], hepatocellular cancer [28], breast cancer [29], esophageal cancer [30], and gastric cancer [31]. As the prognostic value of β-catenin in pancreatic cancer remains controversial, a meta-analysis was needed to explore the issue clearly.…”
Section: Discussionmentioning
confidence: 99%
“…Other gene mutations like RAS and structural changes including insertion/deletion and translocations of RET, PAX8/PPAR have been determined to play a role in clinical course of papillary thyroid carcinoma (4)(5)(6). In recent decade proto-oncogene effect of wnt/ β -catenin pathway and its role in human cancers have been determined (7)(8)(9)(10). Role of β -catenin in propagation, renewal and regeneration of epithelial tumors have also been highlighted.…”
Section: Introductionmentioning
confidence: 99%